Exercise and Redox Status Responses Following Alpha-Lipoic Acid Supplementation in G6PD Deficient Individuals - Georgakouli, Kalliopi (Antioxidants (Basel), 2018)
G6PD deficiency renders cells more susceptible to oxidative insults, while antioxidant dietary supplementation could restore redox balance and ameliorate exercise-induced oxidative stress. To examine the effects of alpha-lipoic acid (ALA) supplementation on redox status indices in G6PD deficient individuals, eight male adults with G6PD deficiency (D) participated in this randomized double-blind placebo-controlled crossover trial. Participants were randomly assigned to receive ALA (600 mg/day) or placebo for 4 weeks separated by a 4-week washout period. Before and at the end of each treatment period, participants exercised following an exhaustive treadmill exercise protocol. Blood samples were obtained before (at rest), immediately after and 1h after exercise for later analysis of total antioxidant capacity (TAC), uric acid, bilirubin, thiobarbituric acid reactive substances (TBARS) and protein carbonyls (PC). ALA resulted in significantly increased resting TAC and bilirubin concentrations. Moreover, TAC increased immediately and 1h after exercise following both treatment periods, whereas bilirubin increased immediately after and 1h after exercise following only ALA. No significant change in uric acid, TBARS or PC was observed at any time point. ALA supplementation for 4 weeks may enhance antioxidant status in G6PD individuals; however, it does not affect redox responses to acute exercise until exhaustion or exercise performance.